A Review of Radiotherapy-Induced Late Effects Research after Advanced Technology Treatments - Newhauser, Wayne D.; de Gonzalez, Amy Berrington; Schulte, Reinhard; Lee, Choonsik (Frontiers in Oncology, 2016)
The number of incident cancers and long-term cancer survivors is expected to increase substantially for at least a decade. Advanced-technology radiotherapies, e.g., using beams of protons and photons, offer dosimetric advantages that theoretically yield better outcomes. In general evidence from controlled clinical trials epidemiology studies are lacking. To conduct these studies, new research methods and infrastructure will be needed. In the paper, we review several key research methods of relevance to late effects after advanced-technology proton-beam and photon-beam radiotherapies. In particular, we focus on the determination of exposures to therapeutic and stray radiation and related uncertainties, with discussion of recent advances in exposure calculation methods, uncertainties, in-silico studies, computing infrastructure, electronic medical records, and risk visualization. We identify six key areas of methodology and infrastructure that will be needed to conduct future outcome studies of radiation late effects.